STUDY OF THE REPRODUCTION OF THE INDIGENOUS SHOR POPULATION OF THE KEMEROVO REGION - Лузина, Фаина Анисимовна; Дорошилова, Анастасия Викторовна; Гуляева, Ольга Николаевна (Medicine in Kuzbass, 2018)
The objective was to study the dynamics of the population number and the reproduction of the indigenous Shorian population of the Kemerovo Region.Materials and methods. The paper used the materials of the population censuses in 2002, 2010, 2015, records of books of household accounting of the rural population in Gornaya Shoria, pedigrees-questionnaires. The total coefficients of birth rate and natural movement of the population were calculated. Statistical processing of the materials was carried out in the standard software package SPSS 21.0.Main results. The negative dynamics of the demographic processes associated with the reproduction of the indigenous Shorian population was revealed: the rate of decline in population number accelerated, the average number of children born as a whole decreased (2002 – 2,590; 2010 – 1,740; 2015 – 1,456 children per 1000 women) and in different age groups of women which testified to the narrowed mode of demographic reproduction of the Shorian ethnic group.Conclusion. The demographic processes of the indigenous Shorian population take place within the framework of the all-Russian and global trends and are associated with the demographic transition from the traditional type to the modern one of the population reproduction. In the Shorians of the Kemerovo Region this process is slower.
Keywords: the Shorians; population reproduction; demographic processes; the Kemerovo Region